2019
DOI: 10.1002/ejp.1368
|View full text |Cite
|
Sign up to set email alerts
|

Altered amygdalar volume and functional connectivity in primary dysmenorrhoea during the menstrual cycle

Abstract: Background Primary dysmenorrhoea (PDM), characterized as menstrual pain without pelvic pathology, is associated with pain‐related negative mood and hormone fluctuations. Previous studies strongly supported the link between pain and negative mood in affected individuals; however, it remains largely unknown in patients with PDM. Methods We focused on the effects how spontaneous pain, negative mood and hormone levels played on the central nervous system in 34 PDM women and 33 matched healthy controls across their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 73 publications
3
35
0
Order By: Relevance
“…and (d) their average cramping pain intensity in the last 6 months was rated >4 (0 = not at all, 10 = the worst pain). The PDM individuals were screened and diagnosed by a gynecologist from the Department of Obstetrics and Gynecology at the First Affiliated Hospital of the Medical College of Xi'an Jiaotong University (L. Yang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and (d) their average cramping pain intensity in the last 6 months was rated >4 (0 = not at all, 10 = the worst pain). The PDM individuals were screened and diagnosed by a gynecologist from the Department of Obstetrics and Gynecology at the First Affiliated Hospital of the Medical College of Xi'an Jiaotong University (L. Yang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Primary dysmenorrhea (PDM) is classified as a chronic pelvic pain syndrome. In female adolescents, it is a very common cyclic menstrual pain without pelvic pathology (Low et al, 2018;L. Yang et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary dysmenorrhea (PDM), a very common type of cyclic menstrual pain without organic causes in female adolescents, induces recurrent, spontaneous, painful and pain-free states (10). Women with PDM have a poorer mood state during menstruation than preovulatory phases (11). Hence, PDM can be used as a great clinical model to study both the effects of long-term menstrual pain on empathy and the difference of the empathy between painful and pain-free states.…”
Section: Introductionmentioning
confidence: 99%
“…Payne et al stated that primary dysmenorrhea (PDM) is associated with enhanced pain sensitivity and temporal summation in adult women, which may reflect the presence of central pain processes [17]. Also, Yang et al [18] concluded that women with PDM had structural and functional abnormalities in the amygdala, which associated with stress hormone levels, pain intensity and negative mood, may reflect disturbed emotional and pain modulation in women with PDM [18]. Dysmenorrhea was considerably higher in girls who were consistently eating fast food.…”
Section: Introductionmentioning
confidence: 99%